Desórdenes Cardiovasculares Asociados a Esteatosis Hepática no Alcohólica - Ramos Sánchez, Marco Antonio (2015)
To assess whether cardiovascular disorders are associated with nonalcoholic hepatic steatosis in patients treated at the Regional Hospital of Trujillo during the period December 2014 to January 2015. MATERIAL AND METHODS: We conducted an observational, analytical, transversal study, which evaluated 110 patients ≥ 18 years of age divided into two groups (55 patients with NASH and 55 patients without this condition) who came for an abdominal ultrasound study where the presence or absence of informing NASH. RESULTS: The mean age of patients in group I was 51.42 ± 9.87 years and group II patients was 31.91 ± 7.33 years (p < 0.001); male gender in groups I and II were 41.82% and 43.64% respectively (p > 0.05). The mean BMI in group I patients was 28.62 ± 2.41 kg / m2 and group II patients was 25.97 ± 1.95 kg / m2 (p <0.001), when BMI was categorized observed that the proportion of obesity in group I and II was of 30.91% and 5.45% respectively (p < 0.001). With regard to the presence of hypertension, coronary heart disease, history of EVC and presence of peripheral arterial disease was observed in group I were present in 14.55%; 3.64%; 1.82% and 12.73% respectively, and in group II were present at 3.64%, 0%, 0% and 1.82% respectively (p < 0.05; p > 0.05; p > 0.05 and p < 0.05 respectively). CONCLUSIONS: The obesity, hypertension and peripheral arterial disease were associated with nonalcoholic hepatic steatosis.